Dynamics of cardiac autonomic regulation during isometric sustained weight test in hypertensive patients (SciELO Preprints, 2021)
Background: The Sustained Weight Test (SWT) is an isometric exercise test that has great practical value for carrying out massive studies on hypertension, however, is insufficient knowledge of the dynamics of cardiac autonomic regulation during this test. The aim of this study was to determine variations in the dynamics of cardiac autonomic regulation and in hemodynamic response during SWT in hypertensive subjects.Methods: A quasi-experimental study was conducted on 15 hypertensive patients of both sexes, paired with 30 normotensive individuals, measuring arterial blood pressure, entropy sample and the Heart Rate Variability (HRV) in time-frequency with the Continuous Wavelet Transform Morlet-type (CWT  morlet) through the electrocardiographic signal of the polygraph AD Instruments in the functional states of Rest and SWT.Results: A significant increase in heart rate and blood pressure was found, as well as a decrease in sample entropy in the functional states of normotensive and hypertensive patients. In hypertensive patients, an early response pattern increased with multiple fluctuations during SWT in the time-frequency analysis of HRV with the CWT morlet.Conclusions: SWT produces an increase in blood pressure, which is more frequent and evident in hypertensive subjects. Cardiac autonomic regulation during SWT increases the sympathetic and decreases the parasympathetic components, manifesting itself in hypertensive patients with a pattern of imbalance in the regulation of both sympathetic and parasympathetic response.